Tele-rehabilitation in Neurological Disorders: A Narrative Synthesis of Efficacy, Accessibility, and Long-Term Impact - Mubsirah Qamar; Tehreem Mukhtar; Yashfa Khalil Malik; Ayesha Sarwar; Hifsa Riaz; Ayesha Rashid (Journal of Health, Wellness and Community Research, 2025)
Background: Neurological disorders such as stroke, Parkinson’s disease, and multiple sclerosis are leading causes of disability worldwide, often resulting in long-term impairments in motor, cognitive, and functional abilities. While conventional rehabilitation is clinically effective, barriers related to mobility, cost, and geographic access limit its availability. Telerehabilitation, the delivery of rehabilitation services via telecommunication technologies, has emerged as a potential solution to these challenges, particularly in the post-pandemic era. Objective: To synthesize evidence from systematic and umbrella reviews on the efficacy, accessibility, and long-term impact of telerehabilitation in neurological disorders. Methods: A narrative synthesis of systematic reviews, meta-analyses, and umbrella reviews published between 2021 and 2025 was conducted using PubMed, Scopus, EMBASE, and Cochrane databases. Eligible studies evaluated telerehabilitation interventions for stroke, Parkinson’s disease, or multiple sclerosis. Outcomes included motor and cognitive function, activities of daily living, quality of life, adherence, accessibility, cost-effectiveness, and long-term independence. Results: Twenty-eight reviews comprising over 14,500 participants were included. Telerehabilitation significantly improved motor outcomes (SMD=0.42, p
Keywords: telerehabilitation; neurological disorders; narrative review; long-term impact